Association between oxidative balance score and serum uric acid and hyperuricemia: a population-based study from the NHANES (2011–2018) - Yang, Yuhao; Wu, Zengxiang; An, Zhenmei; Li, Shuangqing (Frontiers in Endocrinology, 2024)
Background: Oxidative Balance Score (OBS) is a novel indicator of the overall oxidation/antioxidant balance, providing a comprehensive reflection of the body's overall oxidative stress status, with higher OBS suggesting more substantial antioxidant exposures. We aimed to investigate the possible relationship between OBS with serum uric acid (SUA) and hyperuricemia.: Data utilized in this study were sourced from the 2011-2018 National Health and Nutrition Examination Survey (NHANES). Participants under 18 years old, those with ≤16 complete data out of 20 OBS components, incomplete serum uric acid data, and missing covariates were excluded from the analysis. OBS was computed by evaluating 16 nutrients and 4 lifestyle factors, encompassing 5 pro-oxidants and 15antioxidants, guided by a priori knowledge of their relationship with oxidative stress.Results: A total of 1,5096 individuals were included in our analysis with 49.7% being male, and an average age of 49.05 ± 17.56 years. The mean OBS was 19.76 ± 7.17.Hyperuricemia was present in 19.28% of participants. Multivariable logistic regression showed that higher lnOBS quantiles were correlated with lower serum uric acid levels. Compared with the lowest lnOBS quantile, participants in the highest lnOBS quantile had a significant serum uric acid decrease of 16.94 μmol/L for each unit increase in lnOBS ). Similar negative associations were observed in the second-highest and third-highest (β=-11.69, 95% CI: -15.05, -8.34) lnOBS quantiles. The adjusted odds ratios (ORs) for hyperuricemia in Quartiles 1, 2, 3, and 4 were 1.00, 0.84 (95% CI: 0.75, 0.95), 0.78 (95% CI: 0.69, 0.88), and 0.62 (95% CI: 0.55, 0.71), respectively.Compared to Quartile 1, participants in Quartile 4 had a 38% lower prevalence of hyperuricemia. Subgroup analysis and interaction test showed that there was a significant dependence of sex between OBS and serum uric acid (p for interaction <0.05), but not hyperuricemia (p for interaction >0.05). Subgroup analysis stratified by age, BMI, hypertension, diabetes, and hyperlipidemia showed there is no significant dependence on these negative correlations (all p for interaction >0.05).The serum uric acid levels and prevalence of hyperuricemia in US adults exhibited a negative association with OBS.